Karakteristik Kimia dan Organoleptik Cookies Dengan Variasi Tepung Komposit Berbasis Tepung Enbal - Yahauubun, Nanta M; Palijama, Syane; Augustyn, Gelora H (Universitas Pattimura, 2025)
Cookies are a type of biscuit made from soft dough, high in fat, relatively crispy and dense in texture. The flour that is often used in making cookies is wheat flour, therefore, to reduce dependence on the use of wheat flour, an alternative substitute for wheat flour is needed, such as composite flour based on local food ingredients. Cookies using non-wheat flour are usually included in the short dough group. This study aims to determine the best treatment of composite flour based on enbal flour. This study was designed using a Completely Randomized Design (CRD) with one factor, namely the comparison of enbal flour with other flours consisting of 4 levels of treatment, including: T1: MOCAF Flour 50%: Enbal Flour 50%, T2: Sukun Flour 50%: Enbal Flour 50%, T3: Sago Flour 50%: Enbal Flour 50% and T4: Banana Flour 50%: Enbal Flour 50%. The results of the study showed that the cookies with the best treatment were in the treatment of 50% MOCAF Flour: 50% Enbal Flour based on chemical characteristics including water content of 5.16%, ash content of 1.51%, protein content of 5.46%, fat content of 21.3% and carbohydrate content of 66.41%, as well as organoleptic characteristics both hedonic and hedonic quality including color 4.00 (very like) and 3.00 (brown), taste 4.00 (very like) and 1.33 (does not taste of enbal) and texture 4.00 (very like) and 4.00 (very crispy).